Rethinking the skills gap - Thijs van Rens; Roland Rathelot (IZA World of Labor, 2017)
Evidence suggests that productivity would be much higher and unemployment much lower if the supply of and demand for skills were better matched. As a result, skills mismatch between workers (supply) and jobs (demand) commands the ongoing attention of policymakers in many countries. Policies intended to address the persistence of skills mismatch focus on the supply side of the issue by emphasizing worker education and training. However, the role of the demand side, that is, employers' wage-setting practices, garners comparatively little policy attention.
Keywords: J24; J42; J62; J64; J31; 330; skills mismatch; misallocation; productivity; unemployment; wage setting